Comportamento criativo e resolução de problemas: estudo exploratório dos efeitos do reforçamento do variar em respostas precorrentes - Leite, Emerson Ferreira da Costa (2016)
Skinner's (1953; 1969; 1974, 1974) analysis of problem-solving behavior emphasizes the participation of precurrent responses manipulating the environment. Cases in which the solution response and its consequences are not previously known seem to be involved in relationships traditionally called "creativity." Despite these contributions, experiments interested in creative behavior gave little emphasis to precurrent responses. The present study evaluated the effects of reinforcement with contingent points to varying in precurrent responses (VAR PRE) on the solution of problems involving the composition of figures. For this, 12 students were exposed in different orders to a contingency of continuous reinforcement of any formed compositions (Ñ VAR) and to the VAR PRE contingency, both preceded and followed by test sessions (T1, T2, T3) in which there was only reinforcement for problem solving. Especially for the participants exposed to the order of conditions Ñ VAR-VAR PRE, the results showed greater effectiveness on problem solving in VAR PRE condition than the condition Ñ VAR. In the reverse order of conditions the results are less conclusive, sometimes showing greater efficacy in VAR PRE, sometimes in Ñ VAR, which suggests an order effect that favors the second condition presented. The results could not be attributed to differences in the behavioral variability produced by the conditions, and the different measures of variability induce to different conclusions. The effects of the amount of exposure to the experimental task, the experimental history, and the requirement of new behavior by the contingency of problem solving were discussed